(3LhGeY GdLGeYs - (3GdWHQSj, CHh Ydj, Cejf GdOjf, GdaVd Hf GdMSf Hf GdaVd, (B548 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj CcQefG HcJGHg GdcQje(B...(3CeG HYO aEfj deG aQZJ ef cJGHj GdcHjQ aj GdJaSjQ GdehShe (B...s
(3BNQgG (B:s
(3hjfJgj HBNQ ShQI Gdcga, hefgG bhdg(B: (3eG ef CMmO jbQC BNQ Gdcga YfO Gdfhe EdG JjbX aj GdSGYI GdJj jQjOgG(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B5(3,U(B148s
(3GdPQjYI(B:(3L(B5(3,U(B177(3,Qbe(B1195s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs